2017
DOI: 10.1515/aut-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Correlation of Air Permeability and Light Transmission Properties of Woven Cotton Fabrics

Abstract: The aim of this study was to develop statistical models for predicting the air permeability and light transmission properties of woven cotton fabrics and determine the level of correlation between the two parameters. Plain woven fabrics were developed with different warp and weft linear densities, ends per inch and picks per inch. After desizing, scouring, bleaching, drying and conditioning, the air permeability and light transmission properties of the fabric samples were determined. Regression analysis result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…To further elaborate the lower threshold frequency for fabric A2, the optical porosity values of the fabrics are compared and are displayed in Figure 8. Transmission of light through the fabric is an established phenomenon to measure the porosity of fabrics and is known to have strong correlations with the air permeability values [30] (both being the measures to calculate porosity). The average porosity values are 2.9% + 0.48, 2.8% + 0.52 and 2.9% + 0.4 for fabrics FA3, FB3 and FC3, respectively, whereas, the porosity values for the proposed copper covering alignment fabrics are 7.2% + 0.26, 3.2% + 0.38 and 2.9% + 0.59 for FA2, FB2 and FC2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To further elaborate the lower threshold frequency for fabric A2, the optical porosity values of the fabrics are compared and are displayed in Figure 8. Transmission of light through the fabric is an established phenomenon to measure the porosity of fabrics and is known to have strong correlations with the air permeability values [30] (both being the measures to calculate porosity). The average porosity values are 2.9% + 0.48, 2.8% + 0.52 and 2.9% + 0.4 for fabrics FA3, FB3 and FC3, respectively, whereas, the porosity values for the proposed copper covering alignment fabrics are 7.2% + 0.26, 3.2% + 0.38 and 2.9% + 0.59 for FA2, FB2 and FC2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Indirectly from the measurements of reflection or other permeability properties from the referential samples [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Cardamone et al employed digital image analysis technique to analyze fabric structural parameters [8] and Militky et al reported that image analysis could be used for determination of air permeability of various weave structures and fiber types [9]. Whereas Nazir et al developed a statistical model for predicting the air permeability and light transmission properties of woven cotton fabrics and determined the level of correlation between the two parameters [10]. Literature shows that there is a need to understand the effect of yarn structure (produced by different spinning systems)upon cover factor of woven fabrics.…”
Section: Introductionmentioning
confidence: 99%